Human capital [videorecording (DVD)] - Virzì, Paolo; Bruni Tedeschi, Valeria, 1964-; Bentivoglio, Fabrizio, 1957-; Golino, Valeria; Amidon, Stephen (Film Movement series., 2015)
"With a lavish home and beautiful wife, hedge-fund manager Giovanni Bernaschi seemingly has it all. Meanwhile, real-estate agent Dino Ossola struggles to maintain his family's middle-class existence and faces even worse financial straits when his wife announces that she is pregnant with twins. Leveraging his daughter's relationships with Giovanni's son, Dino deceives the bank and manipulates his way into the Bernaschi hedge fund. As the destinies of both families become further entwined, a fateful hit-and-run accident sets in motion a chain of events, triggering dangerous consequences that will change their lives forever."--Container